2017
DOI: 10.18632/oncotarget.15602
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in perihilar and intrahepatic cholangiocarcinoma

Abstract: Cholangiocarcinoma is an aggressive biliary neoplasm lacking effective therapeutic agents. Immunotherapies targeting the PD-L1/PD-1 immune checkpoint have shown encouraging results in solid and hematologic cancers in clinical trials. Response to these immunomodulators is correlated with PD-L1 expression. Our goal was to characterize PD-L1 expression in intra-hepatic (iCCA) and perihilar (pCCA) cholangiocarcinomas, and to correlate our results with clinicopathological features, density of tumor-infiltrating lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 30 publications
6
112
1
3
Order By: Relevance
“…PD-L1 expression was more likely to be seen on peri-tumoral immune cells at tumor edges (n=10) than on tumor cells (n=5). Like other tumor types, poorly-differentiated NECs in our study frequently expressed PD-1 on immune cells, including tumor infiltrating lymphocytes and peritumoral inflammatory cells at tumor edges[1114]. Unexpectedly, we also found that tumor cells in 6 of 37 cases expressed PD-1 at least focally.…”
Section: Discussionsupporting
confidence: 63%
“…PD-L1 expression was more likely to be seen on peri-tumoral immune cells at tumor edges (n=10) than on tumor cells (n=5). Like other tumor types, poorly-differentiated NECs in our study frequently expressed PD-1 on immune cells, including tumor infiltrating lymphocytes and peritumoral inflammatory cells at tumor edges[1114]. Unexpectedly, we also found that tumor cells in 6 of 37 cases expressed PD-1 at least focally.…”
Section: Discussionsupporting
confidence: 63%
“…In this clinical trial, PD‐L1 positivity was defined as staining in 1% of cells in tumour nests or PD‐L1‐positive bands in the stroma as determined with the 22C3 assay . However, data regarding PD‐L1 expression status in extrahepatic biliary tract cancers are still limited, and the frequency of PD‐L1 expression in bile duct cancer has varied among studies (Table ) . This variability may be explained by multiple factors, including assay method, interpretation method, specimen type (biopsy; surgically resected specimen), and patient demographics (including tumour stage) …”
Section: Discussionmentioning
confidence: 99%
“…The most-studied biomarker to date is the PD-1 ligand, PD-L1; any expression of PD-L1 on tumour cells, and/or higher levels of tumour PD-L1 expression have both been associated with sensitivity to immune-checkpoint- inhibitor monotherapy in some tumour types, including melanoma and non-small-cell lung cancer (NSCLC), but with conflicting results in other diseases 160162 . In studies of small numbers of cholangiocarcinoma tumour samples ( n = 54–99), PD-L1 expression has been reported in 9–72% of specimens 163165 , and on 46–63% of immune cells within the tumour microenvironment 164,165 . These data indicate that a substantial proportion of cholangiocarcinomas might be amenable to therapy with PD-1 or PD-L1 inhibitors.…”
Section: Emerging Molecularly-directed Therapiesmentioning
confidence: 99%